Primary tumor-derived systemic nANGPTL4 inhibits metastasis - Hübers, Corinne; Abdul Pari, Ashik Ahmed; Grieshober, Denise; Petkov, Martin; Schmidt, Alexander; Meßmer, Tatjana; Heyer, Christian Moritz; Schölch, Sebastian; Kapel, Stephanie; Gengenbacher, Nicolas; Singhal, Mahak; Schieb, Benjamin; et al. (Journal of experimental medicine, 2022)
Primary tumors and distant site metastases form a bidirectionally communicating system. Yet, the molecular mechanisms of this crosstalk are poorly understood. Here, we identified the proteolytically cleaved fragments of angiopoietin-like 4 (ANGPTL4) as contextually active protumorigenic and antitumorigenic contributors in this communication ecosystem. Preclinical studies in multiple tumor models revealed that the C-terminal fragment (cANGPTL4) promoted tumor growth and metastasis. In contrast, the N-terminal fragment of ANGPTL4 (nANGPTL4) inhibited metastasis and enhanced overall survival in a postsurgical metastasis model by inhibiting WNT signaling and reducing vascularity at the metastatic site. Tracing ANGPTL4 and its fragments in tumor patients detected full-length ANGPTL4 primarily in tumor tissues, whereas nANGPTL4 predominated in systemic circulation and correlated inversely with disease progression. The study highlights the spatial context of the proteolytic cleavage-dependent pro- and antitumorigenic functions of ANGPTL4 and identifies and validates nANGPTL4 as a novel biomarker of tumor progression and antimetastatic therapeutic agent.
Gesehen am 02.11.2022